2020
DOI: 10.1186/s12958-020-00628-6
|View full text |Cite
|
Sign up to set email alerts
|

Corifollitropin alfa for poor responders patients, a prospective randomized study

Abstract: Background: Poor ovarian response remains one of the biggest challenges for reproductive endocrinologists. The introduction of corifollitropin alpha (CFA) offered an alternative option to other gonadotropins for its longer halflife, its more rapid achievement of the threshold and higher FSH levels. We compared two different protocols with CFA, a long agonist and a short antagonist, and a no-CFA protocol. Methods: Patients enrolled fulfilled at least two of the followings: AFC < 5, AMH < 1,1 ng/ml, less than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The leave-one-out sensitivity analysis, conducted by serially excluding each study, confirmed the pooled results for almost all the outcomes, with the two following exceptions. When excluding the study by Fusi et al [24] we obtained a significantly higher cycle cancellation rate in the CFA group (OR 1.39, 95% CI [1.06, 1.81], p = 0.02; 7 RCTs, n = 4285; no heterogeneity: I 2 = 0%, p = 0.53). Fi-…”
Section: Subgroups Analyses and Sensitivity Analysismentioning
confidence: 73%
See 4 more Smart Citations
“…The leave-one-out sensitivity analysis, conducted by serially excluding each study, confirmed the pooled results for almost all the outcomes, with the two following exceptions. When excluding the study by Fusi et al [24] we obtained a significantly higher cycle cancellation rate in the CFA group (OR 1.39, 95% CI [1.06, 1.81], p = 0.02; 7 RCTs, n = 4285; no heterogeneity: I 2 = 0%, p = 0.53). Fi-…”
Section: Subgroups Analyses and Sensitivity Analysismentioning
confidence: 73%
“…Previous meta-analyses have been published with the aim to compare the ovarian stimulation with CFA and daily rFSH [25][26][27][28]. With respect to the latest recently published meta-analysis [28], the strengths of the present study comprise that our data updated the results by including four additional studies [17,21,23,24] and 640 more patients. More to the point, the present meta-analysis also combined the data regarding five outcomes previously not examined by Cozzolino and colleagues (2019) (duration of stimulation, cancellation rate, fertilization rate, implantation rate and miscarriage rate).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations